Performance of titanium oxynitrides in the electrocatalytic oxygen evolution reaction. (November 2016) - Gebauer, C.; Fischer, P.; Wassner, M.; Diemant, T.; Jusys, Z.; Hüsing, N.; Behm, R.J.
Abstract: We report results of a detailed study on the activity and stability of titanium oxynitrides in the oxygen evolution reaction (OER) and their correlation with structure and (surface) composition of these materials, which had been reported as promising catalysts for this reaction and for the reverse oxygen reduction reaction (ORR). Combining electrochemical flow cell measurements with online mass spectrometry analysis (differential electrochemical mass spectrometry) allows us to separate catalytic O2 evolution from other electrochemical reactions such as catalyst oxidation. Materials with different nitridation levels were fabricated via thermal treatment of titanium oxide in gaseous ammonia. The resulting materials, which cover a wide range of O:N ratios, were characterized by X-ray diffraction, elemental carbon-hydrogen-nitrogen analysis, and X-ray photoelectron spectroscopy, yielding information about bulk crystallinity, chemical composition, and surface species present, respectively. They show increasing oxidation current densities starting at about 1.2 V, with a peak maximum at 1.7 V. Online mass spectrometry analysis, however, reveals that this current results from oxidation of the electrode surface rather than from O2 evolution, while O2 evolution occurs only at potentials >1.7 V. Increasing nitride contents were found to increase the electrochemical electrode oxidation reaction, while the onset of O2 evolution is independent of the extent of nitridation. Consequences of these findings on the suitability of these materials as OER catalysts will be discussed. Graphical abstract: Highlights: Controllable synthesis of Ti-oxynitrides via ammonolysis of TiO2 . Strong deviation of bulk and surface composition: TiO2, TiON and TiN species. Oxidation at 1.6 V not related to evolution of O2, proven by mass spectrometry. Irreversible electrooxidation of surface nitride sites in the high potential region.